FOMO Related Impulse Buying on Social Commerce: A Literature Review - Ayyasy, Muhammad Zhafran; Belinda, Karissa Inas; Dirgantara, I Made Bayu (LifeSciFi, 2025)
In the context of modern digital commerce, the Fear of Missing Out (FOMO) phenomenon emerges as an emotional response to social pressure and time urgency, amplified by interactive features in Live Commerce Platforms. Consumers, especially the younger generation, are often trapped in consumption patterns driven by false urgency and social validation. This research examines articles from reputable journals through a Systematic Literature Review (SLR) approach. Thematic analysis shows that FOMO-based marketing strategies such as time-limited promotions, product exclusivity, and social validation trigger the emotional drive of consumers, especially Gen Z, to make impulse buying. Findings also show that customer experience is an important mediating variable that amplifies the FOMO effect. In addition to the psychological and social impacts, ethical aspects were also examined, specifically related to low financial literacy that increases consumers' vulnerability to aggressive FOMO campaigns. It was found that FOMO has potential as a campaign tool for sustainable minimalist consumption, if directed strategically. Through conceptual mapping and comparative discussion across studies, this article offers a theoretical foundation for the development of Sustainable Marketing Strategies that are not only effective, but also ethical and oriented towards sustainable consumption behavior.